Drying of SnO2 hydrogels: effect of the electrolyte - Presecatan, Rui Tadeu [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP] (Elsevier, 1992)
The effect of the electrolyte (NH+ 4, Cl-) on the drying of SnO2 hydrogels was investigated by linear shrinkage, mass loss, gravimetric thermal analysis and infrared spectroscopy. Results show that the drying mechanism for monolithic SnO2 gels is highly dependent on the concentration of the electrolyte solution inside the pores. For higher concentrations, the drying process is governed by capillary forces while for the smaller ones (≤20 mM) syneresis shrinkage becomes predominant just before the end of the first drying period. This phenomenon is related to condensation reaction among the superficial OH groups and may hamper formation of monolithic SnO2. © 1992 Elsevier Science Publishers B.V. All rights reserved.
Keywords: Drying; Electrolytes; Tin compounds; Hydrogels; Monoliyhic gels; Residual electrolyte concentation; Tin oxides; Gels